Pengembangan Media Pembelajaran Interaktif Pada Pembelajaran Berhitung yang disertai dengan mengenal Huruf Alfabet dan Huruf Hijaiyah berbasis Flash - Fathurrahman, Fathurrahman; Wasil, Muhammad; Muslihan, Muslihan (Fakultas Teknik Universitas Hamzanwadi, 2024)
Learning is an activity which is extremely needed to improve someone’s self-development, especially in the teaching and learning process which can be seen every year because learning activities are always changing. This change occurs because technological developments are increasingly rapid day by day, technological developments are so rapid that we cannot miss any information, especially in the field of education. This research aims to develop flash-based learning media for counting and recognizing the alphabet and hijaiyah letters. The preschool of Al-Wasilah is one of the preschools whose learning process still uses the K13 curriculum and the process of counting and recognizing the alphabet and hijaiyah letters is still traditional, which uses pictures or posters and blackboards. Current technological developments should be able to be utilized because they can foster students’ learning. The research method used is research and development with stages of developing learning media and testing learning media, so that it can help increase effectiveness, especially for children aged 2-6 years. By using Adobe Flash, it can improve more effective learning outcomes in the subjects of Numeracy and Recognizing Alphabet Letters and Hijaiyah Letters.